Specific and Rapid Detection of Mycobacterium tuberculosis Complex in Clinical Samples by Polymerase Chain Reaction - Singh, Anamika; Kashyap, Vijendra Kumar (Interdisciplinary Perspectives on Infectious Diseases, 2012)
Background. Tuberculosis, a global health problem and highly prevalent in India, has always been a serious problem with respect to definitive diagnosis. Polymerase chain reaction (PCR) techniques are now widely used for early detection and species differentiation of mycobacteria, but mostly with their own limitations. We aim to detect and differentiate Mycobacterium tuberculosis (Mtb) infections by choosing appropriate target sequences, ideally present in all mycobacterial species (MTB complex) and absent in others. Methods. Amplification of three target sequences from unrelated genes, namely, hsp 65 (165 bp), dnaJ (365 bp), and insertion element IS 6110 (541 bp) by PCR was carried out in clinical samples from suspected cases of tuberculosis/ mycobacterioses and healthy controls. Results. The sensitivity of this method ranged from 73.33% to 84.61%, and the specificity was 80%. The PCR method was significantly better (P=0.03 and P=0.009) than both smear and culture methods. Conclusion. Our trimarker-based PCR method could specifically detect M. tuberculosis and MTB complex infection from that of major pathogenic NTM and nonpathogenic mycobacteria. This method, by well distinguishing between MTB complex and NTM, presented a fast and accurate method to detect and diagnose mycobacterial infections more efficiently and could thereby help in better patient management particularly considering the increase in mycobacterial infections due to emergence of NTM over the past decades.